2022
DOI: 10.3390/plants11151935
|View full text |Cite
|
Sign up to set email alerts
|

Study of Volatile Organic Compounds of Two Table Grapes (cv. Italia and Bronx Seedless) along Ripening in Vines Established in the Aegean Region (Turkey)

Abstract: (1) Background: Italia is a seeded grape variety widely cultivated in the Aegean Region in Turkey, whereas Bronx Seedless is a seedless grape variety, preferred by consumers due to its pink berries and interesting flavor. The goal was to study the volatile compounds of these table grapes throughout berry ripeness. (2) Methods: The volatile compounds were analyzed by GC-MS in six different phenological stages (3) Results: Bronx Seedless grapes presented a higher content of seven terpenes, three aldehydes, one f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Hexanal is an organic compound with a molecular formula of C 6 H 12 O. Hexanal exists as a colourless, highly volatile liquid. Hexanal is naturally produced by plants with high concentrations found in maise (Zea mays) (K. Zhang et al, 2022), tea (Camellia sinensis) (Ho et al, 2015), and black walnut (Juglans nigra) (Lee et al, 2011), while low concentrations found in thornless blackberry (Rubus ulmifolius) (Du et al, 2010) and grapes (Vitis vinifera) (Kaya et al, 2022). The United States Food and Drug Administration (USFDA) has approved hexanal as a food additive with a lethal dose (LD 50 ) of 3,700 mg/kg (Khan & Ali, 2018).…”
Section: Hexanalmentioning
confidence: 99%
“…Hexanal is an organic compound with a molecular formula of C 6 H 12 O. Hexanal exists as a colourless, highly volatile liquid. Hexanal is naturally produced by plants with high concentrations found in maise (Zea mays) (K. Zhang et al, 2022), tea (Camellia sinensis) (Ho et al, 2015), and black walnut (Juglans nigra) (Lee et al, 2011), while low concentrations found in thornless blackberry (Rubus ulmifolius) (Du et al, 2010) and grapes (Vitis vinifera) (Kaya et al, 2022). The United States Food and Drug Administration (USFDA) has approved hexanal as a food additive with a lethal dose (LD 50 ) of 3,700 mg/kg (Khan & Ali, 2018).…”
Section: Hexanalmentioning
confidence: 99%
“…These varieties are grown in Turkey and are of great importance for the country’s grape and wine industry, but they are not commercially cultivated. Pollination and fertilization, being fundamental factors influencing fruit setting volume, are critical considerations for fruit producers aiming to achieve high-quantity and -quality yields in the horticultural industry [ 20 , 21 , 22 , 23 ]. Grapes, distinguished for their delightful taste and versatile applications, hold a important role in global agriculture and culinary traditions [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bronx Seedless) and muscat ( Vitis vinifera L. cv. Italia) tastes are cultivated in different regions of Turkey, such as Central Anatolia Aegean, Southeastern Anatolia, and Marmara [ 25 ]. Italia is a seed variety characterized by a slight muscat flavor of fruits, a vigorous vegetative behavior, and mid-late maturity, whereas Bronx Seedless is a variety that is attracted and preferred by consumers because of its pink berries characterized by strawberry flavor.…”
Section: Introductionmentioning
confidence: 99%